2018
DOI: 10.1186/s12917-018-1591-0
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate improves antioxidant stability in sub-acute ruminal acidosis in dairy goats

Abstract: BackgroundCurrently, little is known about the effect of sodium butyrate (NaB) on oxidative stress following grain-induced sub-acute ruminal acidosis in dairy goats. In the present study, 18 lactating dairy goats implanted with a ruminal cannula and permanent indwelling catheters in the portal and hepatic veins were randomly allocated into 3 treatment groups over 20 weeks: low grain (LG, 40% grain; n = 6), high grain (HG, 60% grain; n = 6) and high grain with sodium butyrate (HG + NaB, 60% grain + NaB; n = 6).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…Our results revealed that high‐SBM levels in the diet might cause oxidative damage in juvenile black sea bream but this damage can be alleviated by TB supplementation, which improves the antioxidant capacity in the serum. A study of the relation between dietary sodium butyrate and antioxidant capacity performed by Ma, Abaker, Bilal, Dai, and Shen () demonstrated that the mechanism by which sodium butyrate supplementation alleviates oxidative damage is partially related to the Nrf2 signalling pathway and suggested that the mRNA levels of the Nrf2 signalling pathway genes upregulated antioxidant enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that high‐SBM levels in the diet might cause oxidative damage in juvenile black sea bream but this damage can be alleviated by TB supplementation, which improves the antioxidant capacity in the serum. A study of the relation between dietary sodium butyrate and antioxidant capacity performed by Ma, Abaker, Bilal, Dai, and Shen () demonstrated that the mechanism by which sodium butyrate supplementation alleviates oxidative damage is partially related to the Nrf2 signalling pathway and suggested that the mRNA levels of the Nrf2 signalling pathway genes upregulated antioxidant enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress induces insulin resistance by impairing insulin signal transduction (36) . Previous studies have shown that administering NaB attenuates oxidative stress in many tissues (37,38) and cells (39) . PI3K and p-AKT play key roles in insulin signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K and p-AKT play key roles in insulin signalling pathway. NaB increases PI3K and p-AKT protein levels (39) and alleviates the oxidative status in sub-acute ruminal acidosis through partial activation of antioxidant enzyme genes (37) . In agreement with these previous findings, we found that NaB restored the hepatic expression of IRS1, PI3K and p-AKT that was down-regulated by high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that the supplementation of SB in MR promotes antioxidant activity and alleviates oxidative stress during the suckling period. The higher levels of serum SOD, CAT and GPX in goat kids of G2 than those of kids of G1 may be related to increasing of ruminal pH and decreasing of lipopolysaccharide levels (Ma, Abaker, Bilal, Dai, & Shen, 2018), and these agents may reduce the inflammatory response and the production of reactive oxygen species (ROS). Besides, other potential mechanisms by which butyrate may enhance enzyme activity and antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%